Factors Affecting the Cost Effectiveness of Antibiotics. (12th January 2011) - Simoens, Steven
Abstract : In an era of spiraling health care costs and limited resources, policy makers and health care payers are concerned about the cost effectiveness of antibiotics. The aim of this study is to draw on published economic evaluations with a view to identify and illustrate the factors affecting the cost effectiveness of antibiotic treatment of bacterial infections. The findings indicate that the cost effectiveness of antibiotics is influenced by factors relating to the characteristics and the use of antibiotics (i.e., diagnosis, comparative costs and comparative effectiveness, resistance, patient compliance with treatment, and treatment failure) and by external factors (i.e., funding source, clinical pharmacy interventions, and guideline implementation interventions). Physicians need to take into account these factors when prescribing an antibiotic and assess whether a specific antibiotic treatment adds sufficient value to justify its costs.